Description of Nebulovena persa Pujade-Villar & Paretas-Martínez gen. n. and sp. n. (Hymenoptera: Cynipoidea: Figitidae: Figitinae ) from Iran, with a key to the genera of Figitinae - Paretas-Martínez, Jordi; Rakhsani, Ehsan; Fathabadi, Khalil; Pujade-Villar, Juli (Zootaxa, 2012)
Nebulovena persa, gen. n. and sp. n. is described from Iran. This is the first record of the subfamily Figitinae from Iran.Nebulovena is distinguished from all other figitines by the veins of the radial cell being nebulous and the head subtrian-gular. The morphology of N. persa is illustrated and compared to other figitines. A key to all genera of Figitinae plus Melanips (currently included in the Aspicerinae) is given and illustrated.